When weather wounds workers: The impact of temperature on workplace accidents - Katharina Drescher; Benedikt Janzen (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2023)
We study the effects of temperature on occupational health using administrative data on Swiss occupational accidents from 1996 to 2019. Our results imply that on hot days (Tmax Ï 30 degrees Celsius) the number of occupational accidents increases by 7.4% and on ice days (Tmax < 0 degrees Celsius) by 6.3%, relative to mild days. We find that extreme temperatures cause an average of 2,600 workplace accidents each year, accounting for 1% of annual accidents. We provide suggestive evidence for insufficient sleep on hot days as a mechanism. While extreme temperatures worsen occupational health, we observe limited labor supply adaption for most workers.
Keywords: I1; J2; Q5; 330; Occupational Health; Labor Supply; Climate Change